Acyclovir in the prevention of duodenal ulcer recurrence. Issue 2 (February 1990) - Rune, S J; Linde, J; Bonnevie, O; Petersen, H D; Bendtsen, F; Wandall, J H; Gluud, C; Eriksen, J; Skovbjerg, H; Vilien, M
Abstract : This study tests the hypothesis that reactivation of a latent herpes simplex virus infection may be a cause of recurrent duodenal ulceration. Patients with recently healed duodenal ulcer were entered into a double blind, randomised study of maintenance treatment with the antiviral drug acyclovir (400 mg bid) versus placebo, to determine if suppression of herpes virus infection would influence the natural history of the ulcer disease. One hundred and fifteen patients entered the trial and 76 patients completed it according to the protocol. Endoscopy was performed when ulcer symptoms recurred and at the end of the 25 week trial period. In the acyclovir group the cumulated relapse rate was 63% compared with 56% in the placebo group (NS). This result suggests that reactivation of herpes simplex virus is not a cause of recurrent duodenal ulcer.